Effects of understory removal and thinning on soil aggregation, and organic carbon distribution in Pinus massoniana plantations in the three Gorges Reservoir area. (April 2021) - Shen, Yafei; Cheng, Ruimei; Xiao, Wenfa; Yang, Shao
Highlights: Soil aggregate and organic C distribution is affected by forest management. In all plots, aggregates ranging in size from 250 to 2000 µm had the highest weight proportion. Soil organic carbon was mainly distributed in macroaggregates. Intensive thinning reduces soil organic carbon content and increases CO2 emissions. Abstract: Forest ecosystems are characterized by the largest terrestrial carbon (C) stocks, play a vital role in global C cycle. Numerous previous studies have documented soil C accumulation and its related contributory factors, and have highlighted the soil physical structure, particularly soil aggregates, as a potential key factor determining the accumulation of C in grasslands or farmlands. At present, however, comparatively little is known regarding the soil aggregation and organic C distribution in plantations following forest management. In this study, we sought to identify the effects of forest management on soil aggregation and organic C distribution in Pinus massoniana plantations in the Three Gorges Reservoir area of China. To this end, we compared soil water-stable aggregates (WSAs), organic C distribution, and organic C chemical composition in the 0–10 cm soil layer of forest plots subjected to the following four treatments: unmanaged intact forest (control: CK), low-intensity thinning (15% thinning: LIT), high-intensity thinning (70% thinning: HIT), and understory removal (all understory shrubs removed: SR). The results indicated that the plantation soil was clearly characterized by macroaggregate and microaggregate structures. Among the WSAs, aggregates ranging in size from 250 to 2000 µm had the highest weight proportion (46.78%–53.87%), whereas silt plus clay-sized particles (<53 μm) had the smallest proportion (2.99% to 5.91%). For all treatment plots, soil organic carbon (SOC) was mainly distributed in macroaggregates (approximately 80%). The macroaggregates were significantly lower under SR and HIT treatments than those in CK treatments ( p  < 0.05). In the SR and thinning treatments (LIT and HIT), the content of aggregate-associated C was significantly reduced compared with that in the CK treatment ( p  < 0.05), whereas the total SOC content significantly decreased only in HIT treatment. We also found that the HIT treatment had the effect of altering soil structure, reducing the relative stability of surface SOC, and enhancing microbial respiration, thereby influencing the soil C storage capacity of P. massoniana plantation soils. These findings will provide a useful reference for reducing soil CO2 emissions under global warming and developing sustainable plantation management strategies in the Three Gorges Reservoir area.